Regional Development Planning Strategy as a Poverty Reduction Solution in Polewali Mandar Regency - IR, Rustan; Nawawi, Juanda; Nara, Nurdin; Abdullah, Muh.Tang (KnE Social Sciences, 2024)
The purpose of this research is to describe regional development planning strategies as a solution to reduce poverty in Polewali Mandar Regency. This research was conducted in Polewali Mandar district from July 2022 – January 2023 by conducting a literature review and Focus Discussion Group with the local government through the Research, Development and Planning Agency of Polewali Mandar Regency, Public Works and Regional Spatial Planning Office, Food Crop Agriculture Service. Based on the results of the study, it can be concluded that poverty alleviation is a priority for the Polewali Mandar district government, bearing in mind that the number of poor people increases every year influenced by topographical and geographical factors in areas that are difficult to reach, so a poverty alleviation strategy is needed as stipulated in Polewali Mandar Regent Regulation No. 25/2009 2020 – 2024 Concerning the Regional Poverty Reduction Strategy for Polewali Mandar Regency. Keywords: planning strategy, regional development, poverty